2014
DOI: 10.1177/1049732314549018
|View full text |Cite
|
Sign up to set email alerts
|

Deservingness and Gratitude in the Context of Heart Transplantation

Abstract: Heart transplantation is now routinely offered as a treatment for end-stage heart failure, and the "gift-of-life" metaphor has become pervasive in this context, forming the foundation on which transplantation discourses rest. In this article, we question organ-as-gift understandings of transplantation. One can also legitimately think of the transplanted organ as a donation, with distinct implications in terms of the transplantation experience for the recipient. We explored the transplantation experience of 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 36 publications
0
35
0
1
Order By: Relevance
“…The identified themes, all concerning psychosocial aspects and practicalities of organ transplantation, were most efficiently categorised chronologically: Pre-transplant, Transplant, and Post-transplant. Papers from seven studies reported results from all three periods [32][33][34][35][36][37][38][39]; the remainder were concerned with one or two periods only, such as the post-transplant experience [29,30,[40][41][42][43][44][45][46][47] or the time surrounding transplantation [33,37,39,48]. Each chronological period had several sub-themes (often repeated in more than one chronological period and often interconnected), which are described below.…”
Section: Resultsmentioning
confidence: 99%
“…The identified themes, all concerning psychosocial aspects and practicalities of organ transplantation, were most efficiently categorised chronologically: Pre-transplant, Transplant, and Post-transplant. Papers from seven studies reported results from all three periods [32][33][34][35][36][37][38][39]; the remainder were concerned with one or two periods only, such as the post-transplant experience [29,30,[40][41][42][43][44][45][46][47] or the time surrounding transplantation [33,37,39,48]. Each chronological period had several sub-themes (often repeated in more than one chronological period and often interconnected), which are described below.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of the gift embodies a reciprocity that can never be repaid (Siminoff & Chillag, ) and assumes the giver must make a sacrifice that has no gain (Rapport & Maggs, ). The meanings associated with the “gift” are multifaceted and can potentially influence perceptions of organ donation in both positive and negative directions (see O'Brien, Donaghue, Walker, & Wood, ; Shaw & Webb, ).…”
Section: Introductionmentioning
confidence: 99%
“…De fato, a análise realizada no presente trabalho identificou a gratidão como central às questões de doação. Isso se confirma em estudos recentes sobre as distintas nuanças da gratidão manifestadas por doadores e receptores na doação de órgãos (O'Brien, Donaghue, Walker, & Wood, 2014), embriões (Scully, Haimes, Mitzkat, Porz, & Rehmann-Sutter, 2012) ou sangue (Snelling, 2014).…”
Section: Discussionunclassified